Moving beyond the GM debate. - Ottoline Leyser (Public Library of Science (PLoS), 2014)
Once again, there are calls to reopen the debate on genetically modified (GM) crops. I find these calls frustrating and unnecessarily decisive. In my opinion the GM debate, on both sides, continues to hamper the urgent need to address the diverse and pressing challenges of global food security and environmental sustainability. The destructive power of the debate comes from its conflation of unrelated issues, coupled with deeply rooted misconceptions of the nature of agriculture.